Glycemic profile and associated factors in indigenous Munduruku, Amazonas. - Hanna Lorena Moraes Gomes (Public Library of Science (PLoS), 2021)
Objective To evaluate the glycemic profile and its association with sociodemographic, anthropometric, clinical and lifestyle factors of Munduruku indigenous people. Method Cross-sectional study with a quantitative and analytical approach, a total of 459 indigenous people (57.1% men, aged 36.3 ± 14.7 years old) belonging to the Munduruku ethnic group from the Kwatá-Laranjal Indigenous Land, in Amazonas, Brazil, were selected by probabilistic sampling in all households in the four most populous villages. Sociodemographic and anthropometric variables, blood pressure levels and lipid profile were evaluated. Fasting capillary blood glucose was measured with a digital device. The associations were assessed by multinomial logistic regression, and p-values≤0.05 were considered significant. Results For pre-diabetes, prevalence was 74.3% and, for diabetes, 12.2%. The variables associated with the risk for pre-diabetes were the following: age (OR = 1.03; 95% CI = 1.00 - 1.06) and obesity (OR = 9.69; 95% CI = 1.28 - 73.58). The positive associations indicating risk for diabetes were as follows: age (OR = 1.05; 95% CI = 1.03 - 1.08), overweight (OR = 4.17; 95% CI = 1.69 - 10.32) and obesity (OR = 35.26; 95% CI = 4.12 - 302.08). Conclusions The risks associated with pre-diabetes and diabetes among the Munduruku indigenous people revealed a worrying index. It is necessary to consider changes in eating habits and lifestyle, as well as possible environmental and social changes that can affect this and other groups, with emphasis on those who live in vulnerable conditions.